Sex ratio and breeding of white-lipped peccaries Tayassu pecari (Artiodactyla: Tayassuidae) in a Costa Rican rain forest - Altrichter, Mariana (2001)
White-lipped peccaries are non-seasonal breeders in South America, but little is known about their reproduction in Central America. There are few studies about the sex ratio of this species in the field. We studied the reproduction and sex ratio of white-lipped peccaries during 200 hours of field observation of four radiomarked and two unmarked herds, from July 1996 to April 1997, in Corcovado National Park, Costa Rica. Sex ratio data of three additional, radiomarked herds observed in 1998 were also included. We recorded numbers of mountings, presence of newborns and numbers of nursing interactions. The peccaries showed a distinct reproductive seasonality, with one mating peak in February and another in July. The greatest number of newborns and the peak in nursing activity were observed during July and August, when fruit availability for the peccaries was high. The adult sex ratio was significantly female biased (1.4:1 - 1.8:1), also in contrast with South American populations.